Ultrasound Examination of the Median Nerve at Different Levels: Inter-rater Reliability Study - Burak Tayyip Dede; Fatih Kılınç; Muhammed Oğuz; Fatih Bağcıer; Ebru Aytekin (Galenos Yayinevi, 2024)
Objective: In this study, we aimed to investigate the inter-rater reliability of the median nerve, evaluated at different levels by ultrasound (US) in asymptomatic subjects. Materials and Methods: A cross-sectional study. This study included 61 healthy controls. The mediolateral and anteroposterior diameters and cross-sectional area (CSA) of the median nerve at the carpal tunnel inlet were measured. The CSA of the median nerves at the carpal tunnel outlet and forearm level was measured. Flattening ratio, wrist-forearm ratio and wrist-forearm difference were calculated. Results: In the inter-rater comparison of the measurements, there was a statistically significant difference only in the carpal tunnel outlet cross sectional area (p<0.048). There was no statistically significant difference between the observers in terms of other measurements (p>0.05). For the median nerve measurement, agreement was also moderate to good inter-rater reliability [intraclass correlation coefficient (ICC) =0.54-0.81] except for the forearm cross sectional area, swelling ratio of the medial nerve. For the median nerve forearm cross sectional area, agreement was excellent inter-rater reliability (ICC =0.91). However, for swelling ratio, agreement was poor interrater reliability (ICC =0.27). Conclusion: In this study, US showed to be a reliable tool for measuring median nerve dimensions in asymptomatic subjects.